Electrochemical devices and electronic devices

By setting an intermediate layer in the electrode of the lithium-ion battery and using an electrolyte containing sulfur and oxygen double bonds, the problems of large internal resistance and safety hazards of lithium-ion batteries are solved, and more efficient charging and discharge and improved safety performance are achieved.

CN115172749BActive Publication Date: 2025-02-11NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210644961.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-15
Publication Date
2025-02-11
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

Lithium-ion batteries have large internal resistance, resulting in limited charging and discharging current, long charging time, and a large amount of heat generated during large-scale charging and discharging, resulting in local overheating, accelerating battery aging and safety hazards.

Method used

An intermediate layer is provided between the electrode current collector and the active material layer. The area ratio of the intermediate layer to the active material layer is in the range of 0.9 to 1.1, and a compound containing sulfur-oxygen double bond is added to the electrolyte.

Benefits of technology

It significantly reduces the DC internal resistance and thickness expansion rate of lithium-ion batteries, improves the safety performance and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003683440610000021
    Figure BDA0003683440610000021
  • Figure BDA0003683440610000023
    Figure BDA0003683440610000023
  • Figure BDA0003683440610000031
    Figure BDA0003683440610000031
Patent Text Reader

Abstract

The present application relates to an electrochemical device and an electronic device. Specifically, the present application provides an electrochemical device, comprising: an electrode and an electrolyte, wherein the electrode comprises a current collector, an intermediate layer located on the current collector, and an active material layer located on the intermediate layer, wherein the intermediate layer and the active material layer have a specific area ratio, and the electrolyte comprises a compound containing a sulfur-oxygen double bond. The electrochemical device of the present application has improved DC internal resistance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application date of October 15, 2020, application number "202011101160.7", and invention name "Electrochemical Device and Electronic Device". Technical Field

[0002] The present application relates to the field of energy storage, and in particular to an electrochemical device and an electronic device, in particular a lithium-ion battery. Background Art

[0003] With the development of technology and the increase in demand for mobile devices, people's demands for electrochemical devices (such as lithium-ion batteries) are also increasing. While pursuing longer battery life, higher requirements are placed on the performance of lithium-ion batteries, especially the safety performance of lithium-ion batteries.

[0004] Lithium-ion batteries generally have the following deficiencies or problems: the internal resistance of the battery is relatively large, and the current allowed for charging and discharging is small, resulting in a long charging time (for example, slow charging requires at least 3.5 hours, and fast charging requires at least 30 minutes). When lithium-ion batteries are charged and discharged at a high rate, they will generate a lot of heat due to the internal resistance of the battery. Due to the lack of effective means to evenly dissipate heat from lithium-ion batteries, the inside of lithium-ion batteries will be locally overheated, which not only accelerates the aging of lithium-ion batteries, causing the decline of battery capacity and power performance, but also causes safety hazards such as expansion, deformation, and even explosion of lithium-ion batteries.

[0005] In view of the above, there is a real need to provide an electrochemical device and an electronic device with improved performance. Summary of the invention

[0006] The embodiments of the present application solve at least one problem existing in the related art to at least some extent by providing an electrochemical device and an electronic device with improved DC internal resistance and safety performance.

[0007] In one aspect of the present application, the present application provides an electrochemical device comprising: an electrode and an electrolyte, the electrode comprising a current collector, an intermediate layer located on the current collector, and an active material layer located on the intermediate layer, wherein: the area ratio of the intermediate layer to the active material layer is A, and A is in the range of 0.9 to 1.1; the electrolyte comprises a compound containing sulfur-oxygen double bonds.

[0008] According to an embodiment of the present application, the intermediate layer includes a conductive material, and an average particle size of the conductive material is less than 1 μm.

[0009] According to an embodiment of the present application, the conductive material includes at least one of carbon black, carbon fiber, graphene or carbon nanotube.

[0010] According to an embodiment of the present application, the specific surface area of ​​the conductive material is X m 2 / g, X is in the range of 20 to 300.

[0011] According to an embodiment of the present application, the content of the compound containing sulfur-oxygen double bonds is Y%, based on the weight of the electrolyte, where Y is in the range of 0.01 to 10.

[0012] According to an embodiment of the present application, A and Y satisfy: 0.009≤A×Y≤6.

[0013] According to an embodiment of the present application, X and Y satisfy: 0.2≤X×Y≤200.

[0014] According to an embodiment of the present application, the compound containing a sulfur-oxygen double bond includes at least one of the following compounds: cyclic sulfate, chain sulfate, chain sulfonate, cyclic sulfonate, chain sulfite or cyclic sulfite.

[0015] According to an embodiment of the present application, the compound containing a sulfur-oxygen double bond includes a compound of formula 1:

[0016]

[0017] in:

[0018] W is selected from

[0019] L is selected from a single bond or a methylene group, and two Ls in the same ring structure are not single bonds at the same time;

[0020] m is 1, 2, 3 or 4;

[0021] n is 0, 1 or 2; and

[0022] p is 0, 1, 2, 3, 4, 5 or 6.

[0023] According to an embodiment of the present application, the compound of formula 1 includes at least one of the following:

[0024]

[0025]

[0026] According to an embodiment of the present application, the electrolyte further includes at least one of the following compounds:

[0027] (a) Propionate esters;

[0028] (b) organic compounds having a cyano group;

[0029] (c) lithium difluorophosphate;

[0030] (d) Compound of formula 2:

[0031]

[0032] in:

[0033] R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl;

[0034] L1 and L2 are each independently -(CR 7 R 8 ) n -;

[0035] R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and

[0036] n is 1, 2 or 3.

[0037] According to an embodiment of the present application, the compound of formula 2 includes at least one of the following compounds:

[0038]

[0039] According to an embodiment of the present application, the content of the propionate is a%, based on the weight of the electrolyte, and a is in the range of 10 to 60.

[0040] According to an embodiment of the present application, based on the weight of the electrolyte, the content of the lithium difluorophosphate is b%, and b is in the range of 0.01 to 2.

[0041] According to an embodiment of the present application, Y and b satisfy; 0.01≤Y / b≤100.

[0042] In another aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.

[0043] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION

[0044] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0045] Unless expressly stated otherwise, the following terms used herein have the meanings indicated below.

[0046] In the detailed description and claims, a list of items connected by the term "at least one of" may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements. The term "at least one of" has the same meaning as the term "at least one of."

[0047] As used herein, the term "alkyl" is expected to be a straight chain saturated hydrocarbon structure with 1 to 20 carbon atoms. "Alkyl" is also expected to be a branched or cyclic hydrocarbon structure with 3 to 20 carbon atoms. When specifying an alkyl with a specific carbon number, it is expected to cover all geometric isomers with that carbon number; therefore, for example, "butyl" means including n-butyl, sec-butyl, isobutyl, tert-butyl and cyclobutyl; "propyl" includes n-propyl, isopropyl and cyclopropyl. Alkyl examples include, but are not limited to methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, etc.

[0048] As used herein, the term "halo" refers to that hydrogen atoms in a group are partially or fully substituted by halogen atoms (eg, fluorine, chlorine, bromine or iodine).

[0049] With the widespread use of electrochemical devices (e.g., lithium-ion batteries), their safety performance has received increasing attention. The safety hazards of electrochemical devices are mainly caused by internal overheating. When lithium-ion batteries are charged and discharged at high rates, the large amount of heat generated inside them cannot be dissipated evenly, which will accelerate the aging of lithium-ion batteries and cause safety hazards such as expansion, deformation, and even explosion of lithium-ion batteries.

[0050] The present application solves the above-mentioned problem by providing an intermediate layer between the electrode current collector and the active material layer, wherein the intermediate layer has a specific area ratio to the active material layer, and using an electrolyte solution including a compound containing a sulfur-oxygen double bond in combination.

[0051] In one embodiment, the present application provides an electrochemical device comprising an electrode and an electrolyte as described below.

[0052] I. Electrode

[0053] One feature of the electrochemical device of the present application is that the electrode includes a current collector, an intermediate layer located on the current collector, and an active material layer located on the intermediate layer, and the area ratio of the intermediate layer to the active material layer is A, and A is in the range of 0.9 to 1.1. In some embodiments, A is 0.9, 1.0, 1.1, or in the range consisting of any two of the above values. The intermediate layer can significantly reduce the DC internal resistance and thickness expansion rate of the electrochemical device, and improve the safety of the electrochemical device.

[0054] In some embodiments, the intermediate layer includes a conductive material, and the average particle size of the conductive material is 1 μm or less. In some embodiments, the average particle size of the conductive material is 0.8 μm or less. In some embodiments, the average particle size of the conductive material is 0.7 μm or less. In some embodiments, the average particle size of the conductive material is 0.5 μm or less. In some embodiments, the average particle size of the conductive material is 0.2 μm or less. In some embodiments, the average particle size of the conductive material is 0.1 μm or less. When the average particle size of the conductive material is within the above range, it can not only improve the conductivity at the interface between the negative electrode collector and the negative electrode active material layer, but also blur the interface, thereby improving the adhesion between the two. Conductive materials are generally aggregated in a direction parallel to the surface of the negative electrode collector, and are hardly stacked in a direction perpendicular to the negative electrode collector. In this case, when the average particle size of the conductive material is smaller than the average particle size of the negative electrode active material, the interface containing the conductive material between the negative electrode collector and the negative electrode active material layer is very thin, which can significantly reduce the DC internal resistance and thickness expansion rate of the electrochemical device, and improve the safety of the electrochemical device.

[0055] In some embodiments, the conductive material comprises at least one of carbon black, carbon fiber, graphene, or carbon nanotubes. In some embodiments, the carbon black comprises at least one of acetylene black, furnace black, or Ketjen black.

[0056] In some embodiments, the specific surface area of ​​the conductive material is X m 2 / g, X is in the range of 20 to 300. In some embodiments, X is in the range of 50 to 250. In some embodiments, X is in the range of 80 to 200. In some embodiments, X is in the range of 100 to 150. In some embodiments, X is 20, 50, 80, 100, 120, 150, 180, 200, 250, 280, 300 or in the range consisting of any two of the above values. When the specific surface area of ​​the conductive material is within the above range, it helps to further reduce the DC internal resistance and thickness expansion rate of the electrochemical device and improve the safety of the electrochemical device.

[0057] The specific surface area (BET) of a conductive material can be measured by the following method: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas in which the relative pressure of nitrogen relative to atmospheric pressure is accurately adjusted to 0.3, the measurement is performed by the nitrogen adsorption BET single-point method using the gas flow method.

[0058] The electrode described in the present application can be a positive electrode or a negative electrode.

[0059] positive electrode

[0060] The positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on one or both surfaces of the positive electrode current collector.

[0061] 1. Positive electrode active material layer

[0062] The positive electrode active material layer contains a positive electrode active material, and the positive electrode active material layer can be one layer or multiple layers. Each layer of the multiple layers of positive electrode active material can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed metal ions such as lithium ions.

[0063] There is no particular limitation on the type of positive electrode active material, as long as it can electrochemically absorb and release metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. Examples of positive electrode active materials may include, but are not limited to, lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds.

[0064] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2 and the like, wherein a portion of the transition metal atoms serving as the main body of these lithium transition metal composite oxides are replaced by other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, W, etc. Examples of lithium transition metal composite oxides may include, but are not limited to, LiNi0.5 Mn 0.5 O2、LiNi 0.85 Co 0.10 Al 0.05 O2、LiNi 0.33 C0 0.33 Mn 0.33 O2、LiNi 0.45 Co 0.10 Al 0.45 O2、LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5 O4, etc. Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, wherein a portion of the Mn in LiMn2O4 can be replaced by a transition metal (e.g., LiNi 0.33 Co 0.33 Mn 0.33 O2), part of the Co in LiCoO2 can be replaced by transition metals.

[0065] In some embodiments, the transition metal in the lithium-containing transition metal phosphate compound includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compound includes iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4, wherein a portion of the transition metal atoms as the main body of these lithium transition metal phosphate compounds are replaced by other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.

[0066] In some embodiments, the positive electrode active material includes lithium phosphate, which can improve the continuous charging characteristics of the electrochemical device. There is no limitation on the use of lithium phosphate. In some embodiments, the positive electrode active material and lithium phosphate are mixed. In some embodiments, the content of lithium phosphate is greater than 0.1%, greater than 0.3% or greater than 0.5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is less than 10%, less than 8% or less than 5% relative to the weight of the above-mentioned positive electrode active material and lithium phosphate. In some embodiments, the content of lithium phosphate is within the range formed by any two of the above-mentioned values.

[0067] surface coating

[0068] A substance having a different composition from that of the positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attached substance may include, but are not limited to: oxides such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.

[0069] These surface-attached substances can be attached to the surface of the positive electrode active material by the following methods: a method in which the surface-attached substance is dissolved or suspended in a solvent and then added to the positive electrode active material and dried; a method in which a surface-attached substance precursor is dissolved or suspended in a solvent, added to the positive electrode active material, and then reacted by heating or the like; and a method in which the surface-attached substance is added to the positive electrode active material precursor and then fired simultaneously, etc. In the case of carbon attachment, a method in which a carbon material (e.g., activated carbon, etc.) is mechanically attached can also be used.

[0070] In some embodiments, the content of the surface-attached substance is greater than 0.1 ppm, greater than 1 ppm, or greater than 10 ppm based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is less than 10%, less than 5%, or less than 2% based on the weight of the positive electrode active material layer. In some embodiments, the content of the surface-attached substance is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer.

[0071] By attaching substances to the surface of the positive electrode active material, the oxidation reaction of the electrolyte on the surface of the positive electrode active material can be suppressed, and the life of the electrochemical device can be improved. When the amount of surface-attached substances is too small, the effect cannot be fully demonstrated; when the amount of surface-attached substances is too large, it will hinder the entry and exit of lithium ions, and the resistance may sometimes increase.

[0072] In the present application, a positive electrode active material in which a substance having a different composition from the positive electrode active material is attached to the surface of the positive electrode active material is also referred to as a “positive electrode active material”.

[0073] shape

[0074] In some embodiments, the shape of the positive electrode active material particles includes, but is not limited to, block, polyhedron, sphere, ellipsoid, plate, needle and column, etc. In some embodiments, the positive electrode active material particles include primary particles, secondary particles or a combination thereof. In some embodiments, the primary particles can be agglomerated to form secondary particles.

[0075] Tap density

[0076] In some embodiments, the tap density of the positive electrode active material is greater than 0.5 g / cm 3, greater than 0.8g / cm 3 Or greater than 1.0g / cm 3 . When the tap density of the positive electrode active material is within the above range, the amount of dispersion medium and the required amount of conductive material and positive electrode binder required for the formation of the positive electrode active material layer can be suppressed, thereby ensuring the filling rate of the positive electrode active material and the capacity of the electrochemical device. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density, the better, and there is no particular upper limit. In some embodiments, the tap density of the positive electrode active material is less than 4.0 g / cm 3 , less than 3.7g / cm 3 or less than 3.5g / cm 3 When the tap density of the positive electrode active material has the upper limit as described above, a decrease in load characteristics can be suppressed.

[0077] The tap density of the positive electrode active material can be calculated by placing 5 g to 10 g of the positive electrode active material powder in a 10 mL glass measuring cylinder and vibrating the cylinder 200 times with a stroke of 20 mm to obtain the powder packing density (tap density).

[0078] Median particle size (D50)

[0079] When the positive electrode active material particles are primary particles, the median particle size (D50) of the positive electrode active material particles refers to the primary particle size of the positive electrode active material particles. When the primary particles of the positive electrode active material particles aggregate to form secondary particles, the median particle size (D50) of the positive electrode active material particles refers to the secondary particle size of the positive electrode active material particles.

[0080] In some embodiments, the median particle size (D50) of the positive electrode active material particles is greater than 0.3 μm, greater than 0.5 μm, greater than 0.8 μm or greater than 1.0 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is less than 30 μm, less than 27 μm, less than 25 μm or less than 22 μm. In some embodiments, the median particle size (D50) of the positive electrode active material particles is within the range composed of any two of the above values. When the median particle size (D50) of the positive electrode active material particles is within the above range, a positive electrode active material with a high tap density can be obtained, which can inhibit the reduction of the performance of the electrochemical device. On the other hand, in the preparation process of the positive electrode of the electrochemical device (that is, when the positive electrode active material, the conductive material and the binder are slurried with a solvent and coated in a thin film), problems such as streaks can be prevented. Here, by mixing two or more positive electrode active materials with different median particle sizes, the filling property during the preparation of the positive electrode can be further improved.

[0081] The median particle size (D50) of the positive electrode active material particles can be measured using a laser diffraction / scattering particle size distribution measuring device: when using LA-920 manufactured by HORIBA as a particle size distribution meter, a 0.1% sodium hexametaphosphate aqueous solution is used as the dispersion medium used in the measurement, and the measurement refractive index is set to 1.24 after 5 minutes of ultrasonic dispersion.

[0082] Average primary particle size

[0083] In the case where the primary particles of the positive electrode active material particles agglomerate to form secondary particles, in some embodiments, the average primary particle size of the positive electrode active material is greater than 0.05 μm, greater than 0.1 μm or greater than 0.5 μm. In some embodiments, the average primary particle size of the positive electrode active material is less than 5 μm, less than 4 μm, less than 3 μm or less than 2 μm. In some embodiments, the average primary particle size of the positive electrode active material is within the range formed by any two of the above values. When the average primary particle size of the positive electrode active material is within the above range, the powder filling and specific surface area can be ensured, the reduction of battery performance can be suppressed, and appropriate crystallinity can be obtained, thereby ensuring the reversibility of charging and discharging of the electrochemical device.

[0084] The average primary particle size of the positive electrode active material can be obtained by observing the image obtained by scanning electron microscopy (SEM): in the SEM image with a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice obtained by the left and right boundary lines of the primary particles relative to the horizontal straight line is calculated, and the average value is calculated to obtain the average primary particle size.

[0085] Specific surface area (BET)

[0086] In some embodiments, the specific surface area (BET) of the positive electrode active material is greater than 0.1 m 2 / g, greater than 0.2m 2 / g or greater than 0.3m 2 In some embodiments, the specific surface area (BET) of the positive electrode active material is less than 50 m 2 / g, less than 40m 2 / g or less than 30m 2 / g. In some embodiments, the specific surface area (BET) of the positive electrode active material is within the range formed by any two of the above values. When the specific surface area (BET) of the positive electrode active material is within the above range, the performance of the electrochemical device can be ensured, and the positive electrode active material can have good coating properties.

[0087] The specific surface area (BET) of the positive electrode active material can be measured by the following method: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas with a relative pressure value of nitrogen accurately adjusted to 0.3 relative to atmospheric pressure, the sample is measured by the nitrogen adsorption BET single-point method using the gas flow method.

[0088] Positive electrode conductive material

[0089] There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0090] In some embodiments, the content of the positive electrode conductive material is greater than 0.01%, greater than 0.1%, or greater than 1%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode conductive material is less than 10%, less than 8%, or less than 5%, based on the weight of the positive electrode active material layer. When the content of the positive electrode conductive material is within the above range, sufficient conductivity and capacity of the electrochemical device can be ensured.

[0091] Positive electrode binder

[0092] There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode active material layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above positive electrode binders can be used alone or in any combination.

[0093] In some embodiments, the content of the positive electrode binder is greater than 0.1%, greater than 1%, or greater than 1.5%, based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode binder is less than 10%, less than 5%, less than 4%, or less than 3%, based on the weight of the positive electrode active material layer. When the content of the positive electrode binder is within the above range, the positive electrode can have good conductivity and sufficient mechanical strength, and the capacity of the electrochemical device is guaranteed.

[0094] Solvents

[0095] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, water and mixed media of alcohol and water. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N, N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.

[0096] Thickener

[0097] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.

[0098] In some embodiments, the content of the thickener is greater than 0.1%, greater than 0.2% or greater than 0.3% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is less than 5%, less than 3% or less than 2% based on the weight of the positive electrode active material layer. In some embodiments, the content of the thickener is within the range of any two of the above values ​​based on the weight of the positive electrode active material layer. When the content of the thickener is within the above range, the positive electrode slurry can have good coating properties, and the capacity reduction and resistance increase of the electrochemical device can be suppressed.

[0099] Content of positive electrode active material

[0100] In some embodiments, the content of the positive electrode active material is greater than 80%, greater than 82%, or greater than 84% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is less than 99% or less than 98% based on the weight of the positive electrode active material layer. In some embodiments, the content of the positive electrode active material is within the range of any two arrays above based on the weight of the positive electrode active material layer. When the content of the positive electrode active material is within the above range, the capacitance of the positive electrode active material in the positive electrode active material layer can be ensured, and the strength of the positive electrode can be maintained.

[0101] Density of the positive electrode active material layer

[0102] The positive electrode active material layer obtained by coating and drying may be compacted by a manual press or a roller press to increase the packing density of the positive electrode active material. In some embodiments, the density of the positive electrode active material layer is greater than 1.5 g / cm 3 , greater than 2g / cm 3 or greater than 2.2g / cm 3 In some embodiments, the density of the positive electrode active material layer is less than 5 g / cm 3 , less than 4.5g / cm 3 or less than 4g / cm 3 In some embodiments, the density of the positive electrode active material layer is within the range formed by any two of the above values. When the density of the positive electrode active material layer is within the above range, the electrochemical device can have good charge and discharge characteristics, while suppressing the increase of resistance.

[0103] Thickness of positive electrode active material layer

[0104] The thickness of the positive electrode active material layer refers to the thickness of the positive electrode active material layer on either side of the positive electrode current collector. In some embodiments, the thickness of the positive electrode active material layer is greater than 10 μm or greater than 20 μm. In some embodiments, the thickness of the positive electrode active material layer is less than 500 μm or less than 450 μm.

[0105] Method for producing positive electrode active material

[0106] The positive electrode active material can be manufactured using a common method for manufacturing inorganic compounds. In order to make a spherical or ellipsoidal positive electrode active material, the following manufacturing method can be used: dissolve or crush the raw material of the transition metal and disperse it in a solvent such as water, adjust the pH while stirring, make a spherical precursor and recover it, dry it as needed, add a Li source such as LiOH, Li2CO3, LiNO3, and sinter it at a high temperature to obtain a positive electrode active material.

[0107] 2. Positive electrode current collector

[0108] There is no particular limitation on the type of positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.

[0109] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the form of the positive electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector may include, but is not limited to, carbon plate, carbon film, carbon cylinder, etc. In some embodiments, the positive electrode current collector is a metal foil. In some embodiments, the metal foil is mesh-shaped. The thickness of the metal foil is not particularly limited. In some embodiments, the thickness of the metal foil is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal foil is less than 1 mm, less than 100 μm, or less than 50 μm. In some embodiments, the thickness of the metal foil is within the range composed of any two of the above values.

[0110] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode active material layer, the surface of the positive electrode current collector may include a conductive additive. Examples of the conductive additive may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.

[0111] The thickness ratio of the positive electrode active material layer to the positive electrode current collector refers to the thickness of the single-sided positive electrode active material layer divided by the thickness of the positive electrode current collector, and its value is not particularly limited. In some embodiments, the thickness ratio is less than 50, less than 30, or less than 20. In some embodiments, the thickness ratio is greater than 0.5, greater than 0.8, or greater than 1. In some embodiments, the thickness ratio is within the range of any two of the above values. When the thickness ratio is within the above range, the heat release of the positive electrode current collector during high current density charging and discharging can be suppressed, and the capacity of the electrochemical device can be ensured.

[0112] 3. Method of making positive electrode

[0113] The positive electrode can be made by forming a positive electrode active material layer containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.

[0114] negative electrode

[0115] The negative electrode includes a negative electrode current collector and a positive electrode active material layer disposed on one or both surfaces of the negative electrode current collector, and the negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer can be one or more layers, and each layer of the multi-layer negative electrode active material can contain the same or different negative electrode active materials. The negative electrode active material is any substance that can reversibly embed and deintercalate metal ions such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0116] As a current collector for holding the negative electrode active material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.

[0117] In the case where the negative electrode current collector is a metal material, the negative electrode current collector may include, but is not limited to, metal foil, metal cylinder, metal strip, metal plate, metal film, metal mesh, stamped metal, foamed metal, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil based on a rolling method or an electrolytic copper foil based on an electrolytic method.

[0118] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector is within the range of any two of the above values.

[0119] There is no particular limitation on the negative electrode active material, as long as it can reversibly absorb and release lithium ions. Examples of negative electrode active materials may include, but are not limited to, carbon materials such as natural graphite and artificial graphite; metals such as silicon (Si) and tin (Sn); or oxides of metal elements such as Si and Sn. Negative electrode active materials may be used alone or in combination.

[0120] The negative electrode active material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0121] The negative electrode can be prepared by applying a negative electrode mixture slurry containing a negative electrode active material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode active material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.

[0122] II. Electrolyte

[0123] The electrolyte used in the electrochemical device of the present application includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolyte used in the electrochemical device of the present application further includes an additive.

[0124] Another feature of the electrochemical device of the present application is that the electrolyte includes a compound containing a sulfur-oxygen double bond.

[0125] In some embodiments, the compound containing a sulfur-oxygen double bond comprises at least one of the following compounds: cyclic sulfate, chain sulfate, chain sulfonate, cyclic sulfonate, chain sulfite, or cyclic sulfite.

[0126] In some embodiments, the cyclic sulfates include, but are not limited to, one or more of the following: 1,2-ethylene glycol sulfate, 1,2-propylene glycol sulfate, 1,3-propylene glycol sulfate, 1,2-butylene glycol sulfate, 1,3-butylene glycol sulfate, 1,4-butylene glycol sulfate, 1,2-pentanediol sulfate, 1,3-pentanediol sulfate, 1,4-pentanediol sulfate, 1,5-pentanediol sulfate, and the like.

[0127] In some embodiments, the chain sulfate ester includes, but is not limited to, one or more of the following: dimethyl sulfate, ethyl methyl sulfate, diethyl sulfate, and the like.

[0128] In some embodiments, the linear sulfonate includes, but is not limited to, one or more of the following: fluorosulfonates such as methyl fluorosulfonate and ethyl fluorosulfonate, methyl methanesulfonate, ethyl methanesulfonate, butyl dimethanesulfonate, methyl 2-(methylsulfonyloxy)propionate and ethyl 2-(methylsulfonyloxy)propionate, and the like.

[0129] In some embodiments, the cyclic sulfonate includes, but is not limited to, one or more of the following: 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone Esters, 1-fluoro-2-propylene-1,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 3-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butane sultone, 1,5-pentane sultone, methylene methanedisulfonate and ethylene methanedisulfonate, etc.

[0130] In some embodiments, the linear sulfite includes, but is not limited to, one or more of the following: dimethyl sulfite, ethyl methyl sulfite, diethyl sulfite, and the like.

[0131] In some embodiments, the cyclic sulfite includes, but is not limited to, one or more of the following: 1,2-ethylene glycol sulfite, 1,2-propylene glycol sulfite, 1,3-propylene glycol sulfite, 1,2-butylene glycol sulfite, 1,3-butylene glycol sulfite, 1,4-butylene glycol sulfite, 1,2-pentanediol sulfite, 1,3-pentanediol sulfite, 1,4-pentanediol sulfite, 1,5-pentanediol sulfite, and the like.

[0132] In some embodiments, the compound containing a sulfur-oxygen double bond comprises a compound of Formula 1:

[0133]

[0134] in:

[0135] W is selected from

[0136] L is selected from a single bond or a methylene group, and two Ls in the same ring structure are not single bonds at the same time;

[0137] m is 1, 2, 3 or 4;

[0138] n is 0, 1 or 2; and

[0139] p is 0, 1, 2, 3, 4, 5 or 6.

[0140] In some embodiments, the compound of Formula 1 includes at least one of the following:

[0141]

[0142] In some embodiments, the content of the compound containing sulfur-oxygen double bonds is Y%, based on the weight of the electrolyte, and Y is in the range of 0.01 to 10. In some embodiments, Y is in the range of 0.1 to 8. In some embodiments, Y is in the range of 0.5 to 5. In some embodiments, Y is in the range of 1 to 3. In some embodiments, Y is 0.01, 0.05, 0.1, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or in the range consisting of any two of the above values. When the content of the compound containing sulfur-oxygen double bonds in the electrolyte is within the above range, it helps to further reduce the DC internal resistance and thickness expansion rate of the electrochemical device and improve the safety of the electrochemical device.

[0143] In some embodiments, the content Y% of the compound containing sulfur-oxygen double bonds in the electrolyte and the area ratio A of the intermediate layer to the active material layer satisfy: 0.009≤A×Y≤6. In some embodiments, 0.01% A×Y≤5. In some embodiments, 0.05% A×Y≤3. In some embodiments, 0.1% A×Y≤2. In some embodiments, 0.5% A×Y≤1. In some embodiments, A×Y is 0.009, 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6 or within the range consisting of any two of the above values. When the content Y% of the compound containing sulfur-oxygen double bonds in the electrolyte and the area ratio A of the intermediate layer to the active material layer satisfy the above relationship, the DC internal resistance and thickness expansion rate of the electrochemical device can be further reduced, and the safety of the electrochemical device can be improved.

[0144] In some embodiments, the content of the compound containing sulfur-oxygen double bonds in the electrolyte is Y% and the specific surface area of ​​the conductive material is X m 2 / g satisfies: 0.2≤X×Y≤200. In some embodiments, 0.5≤X×Y≤.50. In some embodiments, 1 in X×Y≤-10. In some embodiments, 5 in X×Y≤-0. In some embodiments, 10-X×Y≤00. In some embodiments, X×Y is 0.2, 0.5, 1, 5, 10, 20, 50, 80, 100, 120, 150, 180, 200 or in a range consisting of any two of the above values. When the content of the compound containing sulfur-oxygen double bonds in the electrolyte is Y% and the specific surface area of ​​the conductive material is X m 2 When the above relationship is satisfied, the DC internal resistance and thickness expansion rate of the electrochemical device can be further reduced, thereby improving the safety of the electrochemical device.

[0145] In some embodiments, the electrolyte further comprises at least one of the following compounds:

[0146] (a) Propionate esters;

[0147] (b) organic compounds having a cyano group;

[0148] (c) lithium difluorophosphate;

[0149] (d) Compound of formula 2:

[0150]

[0151] in:

[0152] R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl;

[0153] L1 and L2 are each independently -(CR 7 R 8 ) n -;

[0154] R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and

[0155] n is 1, 2 or 3.

[0156] (a) Propionate

[0157] In some embodiments, the propionate ester comprises a compound of Formula 3:

[0158]

[0159] in:

[0160] R 1 Selected from ethyl or halogenated ethyl,

[0161] R 2 Selected from C1-C6 alkyl or C1-C6 haloalkyl.

[0162] In certain embodiments, the propionic ester includes, but is not limited to, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, amyl propionate, halogenated methyl propionate, halogenated ethyl propionate, propyl propionate, halogenated butyl propionate and amyl propionate. In certain embodiments, the propionic ester is selected from at least one of methyl propionate, ethyl propionate, propyl propionate, butyl propionate and amyl propionate. In certain embodiments, the halogen group in the halogenated methyl propionate, halogenated ethyl propionate, propyl propionate, halogenated butyl propionate and amyl propionate is selected from one or more of fluorine group (-F), chlorine group (-Cl), bromine group (-Br) and iodine group (-I). In certain embodiments, the halogen group is a fluorine group (-F), which can achieve more excellent effect.

[0163] In some embodiments, the content of the propionate ester is 10% to 60% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 15% to 55% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 30% to 50% based on the weight of the electrolyte. In some embodiments, the content of the propionate ester is 30% to 40% based on the weight of the electrolyte. Using propionate esters with the above content can achieve better results.

[0164] (b) Compounds having a cyano group

[0165] In some embodiments, the compound having a cyano group includes, but is not limited to, one or more of the following: succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, diethylene glycol di(2-cyanoethyl)ether, triethylene glycol di(2-cyanoethyl)ether, tetraethylene glycol di(2-cyanoethyl)ether, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl)ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexatriconitrile, 1,2,6-hexatriconitrile , 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane and 1,2,5-tris(cyanoethoxy)pentane.

[0166] The above-mentioned compounds having a cyano group can be used alone or in any combination. If the electrolyte contains two or more compounds having a cyano group, the content of the compound having a cyano group refers to the total content of the two or more compounds having a cyano group. In some embodiments, based on the weight of the electrolyte, the content of the compound having a cyano group is 0.1% to 15%. In some embodiments, based on the weight of the electrolyte, the content of the compound having a cyano group is 0.5% to 10%. In some embodiments, based on the weight of the electrolyte, the content of the compound having a cyano group is 1% to 8%. In some embodiments, based on the weight of the electrolyte, the content of the compound having a cyano group is 3% to 5%.

[0167] (c) Lithium difluorophosphate (LiPO2F2)

[0168] In some embodiments, the content of lithium difluorophosphate is b%, based on the weight of the electrolyte, and b is in the range of 0.01 to 2. In some embodiments, b is in the range of 0.05 to 1.5. In some embodiments, b is in the range of 0.1 to 1. In some embodiments, b is in the range of 0.3 to 0.5. In some embodiments, b is 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2 or in the range consisting of any two of the above values. When the content of lithium difluorophosphate in the electrolyte is within the above range, the DC internal resistance and thickness expansion rate of the electrochemical device can be further reduced, and the safety of the electrochemical device can be improved.

[0169] In some embodiments, the content Y% of the compound containing sulfur-oxygen double bonds in the electrolyte and the content b% of lithium difluorophosphate satisfy 0.01≤Y / b≤100. In some embodiments, 0.05≤Y / b≤80. In some embodiments, 0.1≤Y / b≤50. In some embodiments, 0.5≤Y / b≤20. In some embodiments, 1 is Y / b≤10. In some embodiments, Y / b is 0.01, 0.05, 0.1, 0.5, 1, 5, 10, 20, 50, 80, 100 or in the range consisting of any two of the above values. When the content Y% of the compound containing sulfur-oxygen double bonds in the electrolyte and the content b% of lithium difluorophosphate satisfy the above relationship, the DC internal resistance and thickness expansion rate of the electrochemical device can be further reduced, and the safety of the electrochemical device can be improved.

[0170] (d) Compound of formula 2

[0171] In some embodiments, the compound of formula 2 includes at least one of the following compounds:

[0172]

[0173] In some embodiments, the content of the compound of formula 2 is 0.01% to 5% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 2 is 0.05% to 3% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 2 is 0.1% to 2% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 2 is 0.5% to 1% based on the weight of the electrolyte. In some embodiments, the content of the compound of formula 2 is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or in the range of any two of the above values ​​based on the weight of the electrolyte.

[0174] Solvents

[0175] In some embodiments, the electrolyte further comprises any non-aqueous solvent known in the prior art that can be used as a solvent for the electrolyte.

[0176] In some embodiments, the non-aqueous solvent includes, but is not limited to, one or more of the following: cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.

[0177] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of the following: ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, the cyclic carbonate has 3-6 carbon atoms.

[0178] In some embodiments, examples of the linear carbonates may include, but are not limited to, one or more of the following: dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), methyl n-propyl carbonate, ethyl n-propyl carbonate, di-n-propyl carbonate and the like. Examples of fluorine-substituted linear carbonates may include, but are not limited to, one or more of the following: bis(fluoromethyl) carbonate, bis(difluoromethyl) carbonate, bis(trifluoromethyl) carbonate, bis(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2-fluoroethyl methyl carbonate, 2,2-difluoroethyl methyl carbonate and 2,2,2-trifluoroethyl methyl carbonate and the like.

[0179] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of the following: one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, part of the hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.

[0180] In some embodiments, the examples of the chain carboxylic acid esters may include, but are not limited to, one or more of the following: methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate, etc. In some embodiments, part of the hydrogen atoms of the chain carboxylic acid ester may be substituted by fluorine. In some embodiments, the examples of the chain carboxylic acid esters substituted by fluorine may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate, etc.

[0181] In some embodiments, examples of the cyclic ether may include, but are not limited to, one or more of the following: tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl 1,3-dioxolane, 4-methyl 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane.

[0182] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of the following: dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1,2-ethoxymethoxyethane, etc.

[0183] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of the following: trimethyl phosphate, triethyl phosphate, dimethyl ethyl phosphate, diethyl methyl phosphate, ethylidene methyl phosphate, ethylidene ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphate, and tris(2,2,3,3,3-pentafluoropropyl) phosphate, etc.

[0184] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of the following: sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be substituted by fluorine.

[0185] In some embodiments, the aromatic fluorine-containing solvent includes, but is not limited to, one or more of the following: fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.

[0186] In some embodiments, the solvent used in the electrolyte of the present application includes cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes an organic solvent selected from the group consisting of the following substances: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, ethyl acetate, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present application includes: ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.

[0187] additive

[0188] In some embodiments, examples of the additive may include, but are not limited to, one or more of the following: fluorocarbonate, ethylene carbonate containing a carbon-carbon double bond, and acid anhydride.

[0189] In some embodiments, the additive is present in an amount of 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the weight of the electrolyte.

[0190] According to an embodiment of the present application, based on the weight of the electrolyte, the content of the propionate is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive.

[0191] In some embodiments, the additive comprises one or more ethylene carbonates containing carbon-carbon double bonds. Examples of the ethylene carbonates containing carbon-carbon double bonds may include, but are not limited to, one or more of the following: vinyl carbonate, methyl vinyl carbonate, ethyl vinyl carbonate, 1,2-dimethyl vinyl carbonate, 1,2-diethyl vinyl carbonate, fluoro vinyl carbonate, trifluoromethyl vinyl carbonate; vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1-ethyl-2-vinyl ethylene carbonate, 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate, 1,1-divinyl ethylene carbonate, 1,2-divinyl ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-diethyl-2-methylene ethylene carbonate, etc. In some embodiments, the ethylene carbonate containing carbon-carbon double bonds includes vinyl carbonate, which is easy to obtain and can achieve more excellent effects.

[0192] In some embodiments, the additive is a combination of fluorocarbonic acid ester and ethylene carbonate containing carbon-carbon double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound containing sulfur-oxygen double bonds. In some embodiments, the additive is a combination of fluorocarbonic acid ester and a compound with 2-4 cyano groups. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic carboxylic acid ester. In some embodiments, the additive is a combination of fluorocarbonic acid ester and cyclic phosphoric acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and sulfonic acid anhydride. In some embodiments, the additive is a combination of fluorocarbonic acid ester and carboxylic acid sulfonic acid anhydride.

[0193] Electrolytes

[0194] The electrolyte is not particularly limited, and any substance known as an electrolyte can be used arbitrarily. In the case of a lithium secondary battery, a lithium salt is generally used. Examples of the electrolyte may include, but are not limited to, inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, and LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; lithium salts such as FSO3Li, CH3SO3Li , CH2FSO3Li, CHF2SO3Li, CF3SO3Li, CF3CF2SO3Li, CF3CF2CF2SO3Li, CF3CF2CF2CF2So3Li and other lithium sulfonate salts; LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide Lithium, LiN(CF3SO2)(C4F9SO2) and other imide lithium salts; LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3 and other methylated lithium salts; (malonate) borate lithium salts such as bis(malonate) borate and difluoro(malonate) borate lithium salts; (malonate) phosphate lithium salts such as tris(malonate) phosphate, difluorobis(malonate) phosphate, tetrafluoro(malonate) phosphate; and LiPF4(CF3)2, LiPF4(C2F5)2, Fluorine-containing organic lithium salts such as LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2; lithium oxalate borate salts such as lithium difluorooxalatoborate and lithium bis(oxalato)borate; lithium oxalate phosphate salts such as lithium tetrafluorooxalato phosphate, lithium difluorobis(oxalato) phosphate and lithium tris(oxalato) phosphate, etc.

[0195] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethanebissulfonyl imide lithium, cyclic 1,3-perfluoropropanebissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(oxalate)borate or lithium difluorobis(oxalato)phosphate, which helps to improve the output power characteristics, high-rate charge and discharge characteristics, high-temperature storage characteristics and cycle characteristics of the electrochemical device.

[0196] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present application. In some embodiments, the total molar concentration of lithium in the electrolyte is greater than 0.3 mol / L, greater than 0.4 mol / L or greater than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within the range formed by any two of the above values. When the electrolyte concentration is within the above range, there will not be too little lithium as a charged particle, and the viscosity can be kept within an appropriate range, thereby easily ensuring good conductivity.

[0197] When more than two electrolytes are used, the electrolyte includes at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a salt selected from the group consisting of monofluorophosphate, oxalate and fluorosulfonate. In some embodiments, the electrolyte includes a lithium salt. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate is within the range of any two of the above values.

[0198] In some embodiments, the electrolyte comprises one or more substances selected from the group consisting of monofluorophosphate, borate, oxalate and fluorosulfonate and one or more salts other than this. As salts other than this, the lithium salts exemplified above can be cited, and in some embodiments, they are LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonyl imide lithium, cyclic 1,3-perfluoropropane bissulfonyl imide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3. In some embodiments, the salt other than this is LiPF6.

[0199] In some embodiments, the content of the other salt is greater than 0.01% or greater than 0.1% based on the weight of the electrolyte. In some embodiments, the content of the other salt is less than 20%, less than 15%, or less than 10% based on the weight of the electrolyte. In some embodiments, the content of the other salt is within the range formed by any two of the above values. The other salt having the above content helps to balance the conductivity and viscosity of the electrolyte.

[0200] In addition to the above-mentioned solvents, additives and electrolyte salts, the electrolyte may contain additional additives such as negative electrode film forming agents, positive electrode protective agents, and anti-overcharge agents as needed. As additives, additives generally used in non-aqueous electrolyte secondary batteries can be used, examples of which may include, but are not limited to, vinylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, etc. These additives can be used alone or in any combination. In addition, the content of these additives in the electrolyte is not particularly limited and can be appropriately set according to the type of the additive, etc. In some embodiments, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5%, based on the weight of the electrolyte.

[0201] III. Isolation Film

[0202] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.

[0203] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.

[0204] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.

[0205] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.

[0206] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.

[0207] The thickness of the isolation membrane is arbitrary. In some embodiments, the thickness of the isolation membrane is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the isolation membrane is within the range formed by any two of the above values. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the electrochemical device can be ensured.

[0208] When a porous material such as a porous sheet or non-woven fabric is used as an isolation membrane, the porosity of the isolation membrane is arbitrary. In some embodiments, the porosity of the isolation membrane is greater than 10%, greater than 15%, or greater than 20%. In some embodiments, the porosity of the isolation membrane is less than 60%, less than 50%, or less than 45%. In some embodiments, the porosity of the isolation membrane is within the range formed by any two of the above values. When the porosity of the isolation membrane is within the above range, insulation and mechanical strength can be ensured, and membrane resistance can be suppressed, so that the electrochemical device has good safety characteristics.

[0209] The average pore size of the isolation membrane is also arbitrary. In some embodiments, the average pore size of the isolation membrane is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the isolation membrane is greater than 0.05 μm. In some embodiments, the average pore size of the isolation membrane is within the range formed by any two of the above values. If the average pore size of the isolation membrane exceeds the above range, short circuit is likely to occur. When the average pore size of the isolation membrane is within the above range, the electrochemical device has good safety characteristics.

[0210] IV. Electrochemical Device Components

[0211] The electrochemical device assembly includes an electrode group, a current collecting structure, an outer casing and a protective element.

[0212] Electrode Group

[0213] The electrode group may be any of a laminated structure formed by laminating the above-mentioned positive electrode and the negative electrode with the above-mentioned separator, and a structure formed by spirally winding the above-mentioned positive electrode and the negative electrode with the above-mentioned separator. In some embodiments, the proportion of the mass of the electrode group in the internal volume of the battery (electrode group occupancy) is greater than 40% or greater than 50%. In some embodiments, the electrode group occupancy is less than 90% or less than 80%. In some embodiments, the electrode group occupancy is within the range formed by any two of the above values. When the electrode group occupancy is within the above range, the capacity of the electrochemical device can be ensured, and at the same time, the reduction of characteristics such as repeated charge and discharge performance and high temperature storage associated with the increase in internal pressure can be suppressed.

[0214] Current collection structure

[0215] There is no particular limitation on the current collection structure. In some embodiments, the current collection structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group is the above-mentioned stacked structure, it is suitable to use a structure formed by bundling the metal core portions of each electrode layer and welding them to the terminal. When the electrode area of ​​a sheet increases, the internal resistance increases, so it is also suitable to set more than two terminals in the electrode to reduce the resistance. When the electrode group is the above-mentioned winding structure, the internal resistance can be reduced by setting more than two lead structures at the positive electrode and the negative electrode respectively, and bundling them at the terminal.

[0216] External shell

[0217] The material of the outer casing is not particularly limited, as long as it is a material that is stable to the electrolyte used. The outer casing can be made of, but not limited to, nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy and other metals, or a laminated film of resin and aluminum foil. In some embodiments, the outer casing is a metal or laminated film of aluminum or aluminum alloy.

[0218] The metal outer casing includes, but is not limited to, a packaged closed structure formed by welding metals to each other by laser welding, resistance welding, and ultrasonic welding; or a riveted structure formed by using the above-mentioned metals through a resin gasket. The outer casing using the above-mentioned laminated film includes, but is not limited to, a packaged closed structure formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above-mentioned resin layers. When the resin layer is thermally bonded to form a closed structure through the collector terminal, due to the bonding between the metal and the resin, a resin with a polar group or a modified resin into which a polar group is introduced can be used as the sandwiched resin. In addition, the shape of the outer casing is also arbitrary, for example, it can be any of cylindrical, square, laminated, button-shaped, large, etc.

[0219] Protection components

[0220] The protection element may be a positive temperature coefficient (PTC) whose resistance increases when abnormal heat is released or excessive current flows, a temperature fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit by causing the internal pressure or internal temperature of the battery to rise sharply when abnormal heat is released. The above protection element may be selected to be an element that does not work in normal use of high current, or may be designed in a form that does not cause abnormal heat release or thermal runaway even if the protection element is not present.

[0221] V. Application

[0222] The electrochemical device of the present application includes any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery or a lithium ion secondary battery.

[0223] The present application further provides an electronic device, which includes the electrochemical device according to the present application.

[0224] The use of the electrochemical device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0225] The preparation of lithium-ion batteries is described below by taking lithium-ion batteries as an example and combining specific embodiments. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application.

[0226] Example

[0227] The following describes the performance evaluation of the examples and comparative examples of the lithium-ion battery according to the present application.

[0228] 1. Preparation of lithium-ion batteries

[0229] 1. Preparation of the middle layer

[0230] The conductive material and styrene-butadiene rubber (SBR) are mixed with deionized water in a mass ratio of 64.5%:35.5%, and stirred evenly to obtain an intermediate layer slurry. The slurry is coated on the positive electrode or negative electrode current collector.

[0231] 2. Preparation of negative electrode

[0232] Artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed with deionized water in a mass ratio of 96%:2%:2%, and stirred evenly to obtain negative electrode slurry. The negative electrode slurry is coated on a 12 μm current collector or an intermediate layer. Drying, cold pressing, cutting and welding of the tabs are performed to obtain the negative electrode.

[0233] 3. Preparation of positive electrode

[0234] Lithium cobalt oxide (LiCoO2), conductive material (Super-P) and polyvinylidene fluoride (PVDF) are mixed with N-methylpyrrolidone (NMP) in a mass ratio of 95%:2%:3%, and stirred evenly to obtain positive electrode slurry. The positive electrode slurry is coated on a 12μm aluminum foil or an intermediate layer, dried, cold pressed, and then cut into pieces and welded to the pole ears to obtain the positive electrode.

[0235] 4. Preparation of electrolyte

[0236] In a dry argon environment, EC, PC and DEC (weight ratio 1:1:1) were mixed, and LiPF6 was added and mixed evenly to form a basic electrolyte, wherein the concentration of LiPF6 was 1.15 mol / L. Different amounts of additives were added to the basic electrolyte to obtain electrolytes of different embodiments and comparative examples.

[0237] The abbreviations and names of the components in the electrolyte are shown in the following table:

[0238]

[0239] 5. Preparation of isolation film

[0240] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0241] 6. Preparation of lithium-ion batteries

[0242] The obtained positive electrode, separator and negative electrode are wound in order and placed in an outer packaging foil, leaving a liquid injection port. The electrolyte is poured from the liquid injection port, packaged, and then subjected to formation, capacity and other processes to obtain a lithium-ion battery.

[0243] 2. Test Method

[0244] 1. Test method for DC internal resistance of lithium-ion battery

[0245] At 25°C, charge the lithium-ion battery to 4.45V at 1C (nominal capacity), then charge at 4.45V at constant voltage until the current is below 0.05C, let it stand for 5 minutes, then discharge at 1C constant current until the cut-off voltage is 3V, then charge at 1C (nominal capacity) at constant current until 4.45V, then charge at 4.45V at constant voltage until the current is below 0.05C, let it stand for 5 minutes, then discharge at 1C constant current until the cut-off voltage is 3V, repeat this cycle 400 times, record the 400th discharge capacity, and adjust the lithium-ion battery to 20% of the required full charge capacity with the actual discharge capacity of the 400th time, and then discharge at a current of 0.3C for 10 seconds. Calculate the DC internal resistance of the lithium-ion battery by the following formula:

[0246] DC internal resistance = (voltage before discharge - voltage at discharge termination) / current

[0247] For each embodiment or comparative example, 15 samples were tested and the average value was taken.

[0248] 2. Test method for thickness expansion rate of lithium-ion batteries

[0249] At 25°C, let the lithium-ion battery stand for 30 minutes, measure its thickness T1, and then start heating at a heating rate of 5°C / min. When the temperature rises to 130°C, keep it for 30 minutes and measure the thickness T2 of the lithium-ion battery. The thickness expansion rate of the lithium-ion battery is calculated by the following formula:

[0250] Thickness expansion ratio = [(T2-T1) / T1] x 100%.

[0251] 3. Test Results

[0252] Table 1 shows the influence of the area ratio of the intermediate layer to the active material layer and the sulfur-oxygen double bond-containing compound in the electrolyte on the DC internal resistance and thickness expansion rate of the lithium-ion battery.

[0253] Table 1

[0254]

[0255] “ / ” means that the feature is not added or not available

[0256] The results show that when the area ratio of the intermediate layer to the active material layer is in the range of 0.9 to 1.1 and the electrolyte includes compounds containing sulfur-oxygen double bonds, the expansion / contraction of the electrode caused by the charging and discharging process can be suppressed, and the compounds containing sulfur-oxygen double bonds help stabilize the surface structure of the electrode, the interface between the active material layer and the current collector, and the interface between the active material layer and the electrolyte, thereby significantly reducing the DC internal resistance and thickness expansion rate of the lithium-ion battery and improving its safety.

[0257] The intermediate layer may be present in the positive electrode or the negative electrode, and may achieve substantially equivalent effects.

[0258] When the content of the compound containing sulfur-oxygen double bonds in the electrolyte is in the range of 0.01% to 10%, the DC internal resistance and thickness expansion rate of the lithium-ion battery can be further reduced, thereby improving its safety.

[0259] When the area ratio A of the intermediate layer to the active material layer and the content of the compound containing sulfur-oxygen double bonds in the electrolyte is Y% and satisfies 0.009≤A×Y≤6, the DC internal resistance and thickness expansion rate of the lithium-ion battery can be further reduced, thereby improving its safety.

[0260] Table 2 shows the average particle size and specific surface area X m of the conductive materials. 2 / g and its relationship with the content of the compound containing sulfur-oxygen double bonds in the electrolyte being Y% on the DC internal resistance and thickness expansion rate of the lithium ion battery. The difference between Examples 2-1 to 2-12 and Example 1-1 is only the parameters listed in Table 2.

[0261] Table 2

[0262]

[0263] The results show that the conductive material can have the following characteristics: average particle size less than 1 μm, specific surface area of ​​20 m 2 / g to 300m 2 / g and specific surface area X m 2 / g and the content Y% of the compound containing sulfur-oxygen double bonds in the electrolyte satisfies 0.2≤X×Y≤200. When the conductive material has at least one of the above characteristics, the DC internal resistance and thickness expansion rate of the lithium ion battery can be further reduced, thereby improving its safety.

[0264] Table 3 further shows the influence of negative electrode active materials on the DC internal resistance and thickness expansion rate of lithium ion battery performance. The difference between Examples 3-1 to 3-5 and Example 1-1 is only the parameters listed in Table 3.

[0265] Table 3

[0266]

[0267] The results show that by adjusting the negative electrode active material, the DC internal resistance and thickness expansion rate of lithium-ion batteries can be further reduced, thereby improving their safety. When the negative electrode active material contains silicon material or hard carbon, the reduction in the DC internal resistance and thickness expansion rate of lithium-ion batteries is particularly significant.

[0268] Table 4 further shows the effect of the positive electrode active material on the DC internal resistance and thickness expansion rate of the lithium ion battery. The difference between Examples 4-1 to 4-5 and Example 1-1 is only the parameters listed in Table 4.

[0269] Table 4

[0270] Positive electrode active material DC internal resistance(mΩ) Thickness expansion rate Example 1-1 Lithium cobalt oxide 185 135% Example 4-1 80% LiCoO2 + 20% NCM (532) 135 95% Example 4-2 NCM(532) 113 89% Example 4-3 80%NCM(532)+20%Lithium manganate 106 91% Example 4-4 Lithium Iron Phosphate 117 95% Embodiment 4-5 80% lithium iron phosphate + 20% lithium iron manganese phosphate 112 84%

[0271] The results show that by adjusting the positive electrode active material, the DC internal resistance and thickness expansion rate of lithium-ion batteries can be further reduced, thereby improving their safety.

[0272] Table 5 shows the effect of electrolyte components on the DC internal resistance and thickness expansion rate of lithium-ion batteries. The difference between Examples 5-1 to 5-31 and Example 1-1 is only the parameters listed in Table 5.

[0273] Table 5

[0274]

[0275]

[0276]

[0277] “ / ” means that the feature is not added or not available

[0278] The results show that when the electrolyte contains propionate, an organic compound with a cyano group, lithium difluorophosphate and / or a compound of formula 2, the DC internal resistance and thickness expansion rate of the lithium-ion battery can be further reduced, thereby improving its safety, based on the area ratio of the intermediate layer to the active material layer being in the range of 0.9 to 1.1 and the electrolyte including a compound containing a sulfur-oxygen double bond.

[0279] Table 6 shows the relationship between the content of sulfur-oxygen double bond compound Y% and the content of lithium difluorophosphate b% in the electrolyte and its influence on the DC internal resistance and thickness expansion rate of lithium ion battery. The difference between Examples 6-1 to 6-11 and Example 1-1 is only that the parameters listed in Table 6

[0280] Table 6

[0281]

[0282] The results show that when the lithium difluorophosphate content in the electrolyte is 0.01% to 2%, the DC internal resistance and thickness expansion rate of the lithium-ion battery can be further reduced, thereby improving its safety.

[0283] When the content Y% of the sulfur-oxygen double bond compound in the electrolyte and the content b% of the lithium difluorophosphate further satisfy 0.01≤Y / b≤100, the DC internal resistance and thickness expansion rate of the lithium ion battery can be further reduced, thereby improving its safety.

[0284] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0285] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising: An electrode and an electrolyte, wherein the electrode comprises a current collector, an intermediate layer located on the current collector, and an active material layer located on the intermediate layer, wherein the intermediate layer comprises a conductive material, wherein: The area ratio of the intermediate layer to the active material layer is A, and A is in the range of 0.9 to 1.1; The electrolyte includes a compound containing a sulfur-oxygen double bond and an organic compound having a cyano group; the organic compound having a cyano group includes at least one of succinonitrile, adiponitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetricarboxylate or 1,2,3-tris(2-cyanoethoxy)propane, Wherein, based on the weight of the electrolyte, the content of the compound containing sulfur-oxygen double bonds is Y%, Y is in the range of 0.01 to 10, and the content of the organic compound having a cyano group is 1% to 8%. 2 . The electrochemical device according to claim 1 , wherein the content of the organic compound having a cyano group is 3% to 5%. 3 . The electrochemical device according to claim 1 , wherein the compound containing a sulfur-oxygen double bond comprises at least one of the following compounds: a cyclic sulfate ester, a chain sulfate ester, a chain sulfonate ester, a cyclic sulfonate ester, a chain sulfite ester, or a cyclic sulfite ester. 4 . The electrochemical device according to claim 2 , wherein the compound containing a sulfur-oxygen double bond comprises at least one of 1,3-propane sultone, 1,2-ethylene glycol sulfate, 1-propylene-1,3-sultone, or methylene methanedisulfonate. The electrochemical device according to claim 1 , wherein A is in the range of 0.9 to 1.

0. The electrochemical device according to claim 1 , wherein A is in the range of 1.0 to 1.

1.

7. The electrochemical device according to claim 1, wherein Y and A satisfy: 0.009≤A×Y≤6. 8 . The electrochemical device according to claim 1 , wherein Y is in the range of 0.01 to 5, and Y and A satisfy: 0.01≤A×Y≤5. 9 . The electrochemical device according to claim 1 , wherein Y is in the range of 0.1 to 3. 10 . The electrochemical device according to claim 1 , wherein Y is in the range of 3 to 5.

11. The electrochemical device according to claim 1, wherein the electrolyte comprises lithium difluorophosphate and / or propionate based on the weight of the electrolyte. 12 . The electrochemical device according to claim 11 , wherein the content of the lithium difluorophosphate is b % based on the weight of the electrolyte, and b is in the range of 0.01 to 2. 13 . The electrochemical device according to claim 11 , wherein the content of the lithium difluorophosphate is b %, based on the weight of the electrolyte, and b is in the range of 0.01 to 1. The electrochemical device according to claim 12 , wherein b is in the range of 1 to 2. 15 . The electrochemical device according to claim 11 , wherein the content of the propionate ester is in the range of 10% to 60% based on the weight of the electrolyte. 16 . The electrochemical device according to claim 11 , wherein the content of the propionate ester is in the range of 15% to 55% based on the weight of the electrolyte. 17 . The electrochemical device according to claim 11 , wherein the content of the propionate ester is in the range of 30% to 50% based on the weight of the electrolyte.

18. The electrochemical device of claim 11, wherein the propionate ester comprises at least one of propyl propionate and ethyl propionate.

19. The electrochemical device according to claim 11, wherein the content of the lithium difluorophosphate is b%, based on the weight of the electrolyte, Y is in the range of 0.01 to 5, and 0.1≤Y / b≤100.

20. The electrochemical device according to claim 11, wherein the content of the lithium difluorophosphate is b%, based on the weight of the electrolyte, b is in the range of 0.01 to 1, and 1≤Y / b≤50. 21 . The electrochemical device according to claim 1 , wherein an average particle size of the conductive material is 1 μm or less.

22. The electrochemical device of claim 1, wherein the conductive material comprises at least one of carbon black, carbon fiber, graphene, or carbon nanotubes.

23. The electrochemical device according to claim 1, wherein the specific surface area of ​​the conductive material is X m 2 / g, X is in the range of 20 to 300.

24. The electrochemical device of claim 23, wherein X is in the range of 80 to 200.

25. The electrochemical device according to claim 23, wherein X and Y satisfy: 0.2≤X×Y≤200.

26. The electrochemical device according to claim 23, wherein Y is in the range of 0.01 to 3 and satisfies: 0.5≤X×Y≤150.

27. The electrochemical device according to claim 1, wherein the compound containing sulfur-oxygen double bonds comprises a compound of formula 1: in: W is selected from L is selected from a single bond or a methylene group, and two Ls in the same ring structure are not single bonds at the same time; m is 1, 2, 3 or 4; n is 0, 1 or 2; and p is 0, 1, 2, 3, 4, 5 or 6.

28. The electrochemical device of claim 27, wherein the compound of Formula 1 comprises at least one of: , Where p is 1.

29. The electrochemical device of claim 1, wherein the electrolyte further comprises at least one of the compounds of formula 2: in: R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are independently hydrogen or C1-C 10 alkyl; L1 and L2 are each independently -(CR 7 R 8 ) n -; R 7 and R 8 are independently hydrogen or C1-C 10 Alkyl; and n is 1, 2 or 3.

30. The electrochemical device according to claim 29, wherein the compound of formula 2 comprises at least one of the following compounds:

31. An electronic device comprising the electrochemical device according to any one of claims 1-30.

Citation Information

Patent Citations

  • Positive electrode for lithium secondary battery and use thereof

    CN102077392A

  • Electrochemical device and electronic device including same

    CN111129498A